Analisis Faktor-Faktor Yang Memengaruhi Kinerja Pegawai Tetap - Umamy, Septy Holisa (Majalah Ilmiah DIAN ILMU, 2023)
Employee performance as an asset that can affect the reputation of the university, therefore there is a need for guidance, empowerment and attention to the factors that affect employee performance. The population of this study were employees at the Muhammadiyah University of Jember, and a sample of 67 used a purposive sampling technique. This type of research is quantitative, using multiple linear regression data analysis techniques with the SPSS Version 25 tool. The findings in this study are that transformational leadership influences the performance of permanent employees, competence influences the performance of permanent employees, perceived of organizational support affect the performance of permanent employees, and job satisfaction affects the performance of permanent employees at the Muhammadiyah University of Jember.